2021
DOI: 10.3390/nu13113781
|View full text |Cite
|
Sign up to set email alerts
|

Association between Milk Intake and Incident Stroke among Japanese Community Dwellers: The Iwate-KENCO Study

Abstract: We aimed to evaluate the association between the milk consumption and incident stroke in a Japanese population, where milk consumption is lower than that of Western countries. In total, 14,121 participants (4253 men and 9868 women) aged 40–69 years, free from cardiovascular diseases (CVD) were prospectively followed for 10.7 years. Participants were categorized into four groups according to the milk intake frequency obtained from a brief-type self-administered diet questionnaire. The adjusted HRs of total stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…110 Among 14 121 adults in the Iwate-KENCO Study in Japan with 478 strokes over 10.7 years of follow-up, intake of 7 to <12 cups of milk per week compared with <2 cups of milk per week was associated with 47% lower hazard of ischemic stroke (95% CI, 12%–68% lower) in females but not in males (7% higher hazard [95% CI, 34% lower–71% higher]). 111 In a meta-analysis of 3 studies including 163 128 adults and 3691 ischemic strokes, the highest category of milk intake was associated with 12% lower risk of ischemic stroke (2%–21% lower; I 2 =0%) compared with the lowest category. 112 …”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
See 1 more Smart Citation
“…110 Among 14 121 adults in the Iwate-KENCO Study in Japan with 478 strokes over 10.7 years of follow-up, intake of 7 to <12 cups of milk per week compared with <2 cups of milk per week was associated with 47% lower hazard of ischemic stroke (95% CI, 12%–68% lower) in females but not in males (7% higher hazard [95% CI, 34% lower–71% higher]). 111 In a meta-analysis of 3 studies including 163 128 adults and 3691 ischemic strokes, the highest category of milk intake was associated with 12% lower risk of ischemic stroke (2%–21% lower; I 2 =0%) compared with the lowest category. 112 …”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…Among 14 121 adults in the Iwate-KENCO Study in Japan with 478 strokes over 10.7 years of follow-up, intake of 7 to <12 cups of milk per week compared with <2 cups of milk per week was associated with 47% lower hazard of ischemic stroke (95% CI, 12%–68% lower) in females but not in males (7% higher hazard [95% CI, 34% lower–71% higher]). 111…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…It also contains Ca and Mg, which are reported to be effective in preventing hypertension [29,30]. A recent cohort study in Japan reported that milk intake of 7 to 12 cups/week decreased the risk of ischemic stroke in women, compared with an intake of < 2 cups/week [31]. However, the average milk consumption is 61.9 g/day [4] and most adults, especially men, do not drink milk regularly.…”
Section: Introductionmentioning
confidence: 99%
“…It also contains Ca and Mg, which are reported to be effective in preventing hypertension [30,31]. A recent cohort study in Japan reported that milk intake of 7 to 12 cups /week decreased the risk of ischemic stroke in women, compared with an intake of <2 cups/week [32]. However, the average milk consumption is 61.9 g/day [4] and most adults, especially men, do not drink milk regularly.…”
Section: Introductionmentioning
confidence: 99%